ANALISIS KUALITAS PELAYANAN KEPERAWATAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS KUTA BARO KABUPATEN ACEH BESAR - Satria Pratama, Angga; Riza, Saiful; Akmalia, Hayatul (Yayasan Healing and Healthcare Education, 2023)
The main contributor to patient satisfactory level is nurses. Nurses have a significant role in determining service quality to meet patient satisfaction at the Community Health Center (Puskesmas). Nurses are the frontline of nursing services for patients and families at the Puskesmas due to the high frequency of meeting with patients. The study aimed to determine the analysis of nursing service quality on patient satisfaction at Kuta Baro Community Health Center in Aceh Besar Regency. This research method used quantitative with an analytical cross-sectional survey approach. The population in this study was 4,957 people, with a sample of 94 people chosen by purposive sampling technique. The instrument in this study used a questionnaire to determine the quality of nursing services on patient satisfaction. The research was conducted at the Kuta Baro Community Health Center of Aceh Besar Regency from June 14 to July 10, 2023. The results of the chi-square analysis showed a p-value of 0.03<0.05, which means the Ha is accepted and H0 is rejected. Thus, there is a correlation between the variables of nursing service quality and patient satisfaction. The nursing services are expected to be more helpful for patients, so the patients become more satisfied with the services provided by nurses.